Mathematical model of laser treatment of the molybdenum coverages inflicted by an elektrosparks method - Radek, N.; Pietraszek, J. (Problems of Tribology, 2014)
The effect of laser treatment on selected properties (microgeometry, microhardness and melting zone of shell) elec-applied coatings can. The study used molybdenum wire with a diameter of 1 as a coating material applied to the sample, which are then melted by laser beam. For the electro-coating production equipment used Bulgarian ELFA-541 model.